The spatiotemporal control of expert tennis players when returning first serves: A perception-action perspective - Navia, J. A.; Avilès, C.; Dicks, M.; Ruiz-Pérez, L. M. (Journal of Sports Sciences, 2022)
The aim of the current experiment was to examine the spatiotemporal control of expert tennis players while executing first service returns within a representative experimental setting. We recruited and tested 12 male expert tennis players in hard courts. A comprehensive analysis of the timing (eleven temporal variables analysed at 300 Hz) and performance success of the return actions were carried out, while simultaneously considering task constraints such as the accuracy and the speed of the serves. Temporal organisation of return actions were scaled relative to the server`s racket-ball contact (5 ms), an adaptation of fly-time of the split-step, which resulted in consistent landings (133 ms), and initiation of lateral movements towards the ball - with no response errors - after the server`s stroke (around 177 ms). Poorer returns occurred when responding to accurate serves accompanied by late trunk movements towards the ball. Returners scaled the timing of the response to the unfolding action of the serve in order to support both spatial and temporal accuracy. These novel findings highlight the significance of the study of fast-ball sports in representative settings and offer further detail on the spatiotemporal control of skilful perception-action.